Application of Heterocycles as an Alternative for the Discovery of New Anti-ulcer Compounds: A Mini-Review - de Lócio, Lucas L.; do Nascimento, Agnis Pâmela Simões; Santos, Mirelly Barbosa; Gomes, Joilly Nilce Santana; de Medeiros e Silva, Yvnni Maria Sales; Albino, Sonaly Lima; dos Santos, Vanda Lúcia; de Moura, Ricardo Olímpio (Current Pharmaceutical Design, 2022)
A peptic ulcer is a lesion located in the esophagus, stomach, and upper intestine, caused by an imbalance between acid secretion and the release of protective mucus. This pathology is prevalent in approximately 14% of the world population and is commonly treated with proton pump inhibitors and type 2 histaminergic receptor antagonists, however, these drugs present concerning side effects that may lead to gastric cancer. In this sense, this research aimed to present the main heterocyclics studied in recent years. The screening method for the choice of articles was based on the selection of publications between 2000 and 2021 present in the Science Direct, Web of Science, Capes, and Scielo databases, by using the descriptors ''new derivatives'', “heterocyclics” “antiulcerogenic”, “gastroprotective” and “antisecretor”. This research showed that the most used rings in the development of anti-ulcer drugs were benzimidazole, quinazoline, thiazole, and thiadiazole. The results also portray several types of modern in silico, in vitro and in vivo assays, as well as the investigation of different mechanisms of action, with emphasis on proton pump inhibition, type 2 histaminergic receptor blockers, potassium competitive acid blockers, type E prostaglandin agonism, anti-secretory activity and anti-oxidant action. Additionally, the review evidenced the presence of the nitrogen atom in the heterocyclic ring as a determinant of the potential of the compound. This research suggests new alternatives for the treatment of gastric lesions, which may be more potent and cause fewer side effects than the currently used, and tend to evolve into more advanced studies in the coming years.
Keywords: anti-ulcer compounds